Geoinformatics and modelling of landslide susceptibility and risk : an RS & GIS-based model building approach in the Eastern Himalaya /: an RS & GIS-based model building approach in the Eastern Himalaya. ([2019]) - Mandal, Sujit; Mondal, Subrata
No abstract available